A multiple covalent crosslinked soft hydrogel for bioseparation. Issue 15 (26th January 2016) - Liu, Zhen; Fan, Liuyin; Xiao, Hua; Cao, Chengxi
Abstract : A multiple covalent crosslinked gel of poly(acrylamide–acrylic acid) was synthesized by using acrylic acid and acrylamide both as a monomer and as a covalent crosslinker. Abstract : A multiple covalent crosslinked gel of poly(acrylamide–acrylic acid) was synthesized by using acrylic acid and acrylamide both as a comonomer and as a covalent crosslinker. The resultant gel showed a high crosslinking degree, tight micropores, but similar softness and marked separation capacity, in contrast to traditional polyacrylamide gels. The gel might serve as a novel matrix in bioseparation.